Mutations of vasopressin receptor 2 including novel L312S have differential effects on trafficking - Tiulpakov, A.; White, C.; Abhayawardana, R.; See, H.; Chan, A.; Seeber, R.; Heng, Julian; Dedov, I.; Pavlos, N.; Pfleger, K. (The Endocrine Society, 2016)
© 2016 by the Endocrine Society. Nephrogenic syndrome of inappropriate antidiuresis (NSIAD) is a genetic disease first described in 2 unrelated male infants with severe symptomatic hyponatremia. Despite undetectable arginine vasopressin levels, patients have inappropriately concentrated urine resulting in hyponatremia, hypoosmolality, and natriuresis. Here, we describe and functionally characterize a novel vasopressin type 2 receptor (V2R) gain-of-function mutation. An L312S substitution in the seventh transmembrane domain was identified in a boy presenting with water-induced hyponatremic seizures at the age of 5.8 years. We show that, compared with wild-type V2R, the L312S mutation results in the constitutive production of cAMP, indicative of the gain-of-function NSIAD profile. Interestingly, like the previously described F229V and I130N NSIAD-causing mutants, this appears to both occur in the absence of notable constitutive ß-arrestin2 recruitment and can be reduced by the inverse agonist Tolvaptan. In addition, to understand the effect of various V2R substitutions on the full receptor “life-cycle,” we have used and further developed a bioluminescence resonance energy transfer intracellular localization assay using multiple localization markers validated with confocal microscopy. This allowed us to characterize differences in the constitutive and ligand-induced localization and trafficking profiles of the novel L312S mutation as well as for previously described V2R gain-of-function mutants (NSIAD; R137C and R137L), loss-of-function mutants (nephrogenic diabetes insipidus; R137H, R181C, and M311V), and a putative silent V266A V2R polymorphism. In doing so, we describe differences in trafficking between unique V2R substitutions, even at the same amino acid position, therefore highlighting the value of full and thorough characterization of receptor function beyond simple signaling pathway analysis.